Risk Factors for Mortality from COVID-19 in Hospitalized Patients: A Logistic Regression Model - Yupari, Irma Luz (2020)
Introduction: The population is susceptible to COVID-19 and knowing the most predominant characteristics and comorbidities of those affected is essential to diminish its effects. Objective: This study analyzed the biological, social and clinical risk factors for mortality in hospitalized patients with COVID-19 in the district of Trujillo, Peru. Methods: A descriptive type of study was made, with a quantitative approach and a correlational, retrospective, cross-sectional design. Data was obtained from the Ministry of Health’s database, with a sample of 64 patients from March to May 2020. Results: 85,71% of the total deceased are male, the most predominant occupation is Retired with an 28,57% incidence, and an average age of 64,67 years. When it came to symptoms of deceased patients, respiratory distress represents the highest percentage of incidence with 90,48%, then fever with 80,95%, followed by malaise in general with 57,14% and cough with 52,38%. The signs that indicated the highest percentage in deaths were dyspnea and abnormal pulmonary auscultation with 47,62%, in Comorbidities patients with cardiovascular disease were found in 42,86% and 14,29% with diabetes. The logistic regression model to predict mortality in hospitalized patients allowed the selection of risk factors such as age, sex, cough, shortness of breath and diabetes. Conclusion: The model is adequate to establish these factors, since they show that a fairly considerable percentage of explained variation would correctly classify 90,6% of the cases.